FAKTOR PENDORONG PERILAKU MEROKOK PADA MAHASISWA DILINGKUNGAN KAMPUS: PENDEKATAN KUALITATIF - Arifin Shaleh Lubis; Putra Apriadi Siregar (Jurnal Kesehatan, 2023)
This research focuses on the driving factors of smoking behavior in college students: a qualitative approach. The research design to be used is descriptive qualitative with a case study approach. The results showed that all informants started smoking when they were still in school. In conclusion, the driving factor for smoking students is due to the pressure that these students get, feeling bored with academic activities and already very addicted to smoking. This makes it difficult for students to stop themselves from smoking on campus. There is also no policy regarding the prohibition of smoking on campus.